PROFIL BERPIKIR PROBABILISTIK SISWA SEKOLAH DASAR (SD) BERKEMAMPUAN MATEMATIKA RENDAH DALAM MENYELESAIKAN TUGAS PROBABILITAS - Dwi Ivayana Sari (Universitas PGRI Semarang, 2015)
The aim of this research was describe the probabilistic thinking profile of elementary students with low academic level in probability task attainment. The research?óÔé¼Ôäós subject was 5th grade students of elementary school. One subject choose with certain criteria, the one who had low math skill and able to communicate fluently. The main instrument of this research was the researcher it self and additional instrument was math test, probability worksheet and interview guidance. The credibility of this research was measured by data triangulation, data reduction, data explanation, data interpretation and making conclusion. The result of this research showed that (1) in the sample space task with experiment used a tools like coin and dice, student gave statistic response, students could list all of space sample. However, in the space sample task with essay/story task, students gave non-statistic response, student gave the answer/reason based on their daily experiences. (2) in the probability task of event with experiment used a tools like spinner, student gave partial statistic responded. However, in the probability task of event with essay form, students gave response with compared the one event to another. This result could be alternative source for curriculum developer, especially in math in elementary level, that elementary students with Keywords: probabilistic thinking, probability task, low academic elementary students